“Health-enhancing” products in the Italian food industry: multinationals and SMEs competing on yogurt - Boesso, G.; Davcik, N. St.; Favotto, F. (AgBioForum, 2009)
The purpose of this research is to present a detailed analytical (qualitative) study of the new “health-enhancing” products in the Italian marketplace, with a focus on both the multinational corporations and the small and medium enterprises (SMEs). The analysis is based on a new products development framework (NPD) which is operationalized by isolating four key strategic elements and other support variables from the literature. The theoretical framework is matched with seven health-food categories and seven yogurts marketed by international corporations and local SMEs in the Italian marketplace. The research provides an in-depth analysis of the emerging strategy in the food industry using the npd theories in a national context (Italy) where the attention to food quality is well-known worldwide and the appeal of the so-called “functional food” seems to be barely—or poorly—investigated.